Studi Tentang Peran Kualitas Kehidupan Kerja, Kepemimpinan dan Persepsi Dukungan Organisasi Terhadap Komitmen Organisasi - Didit Darmawan; Rahayu Mardikaningsih (Universitas Nusantara PGRI Kediri, 2021)
Organizational commitment is a topic that continues to grow because it is assessed by academics and practitioners as an important variable to determine employee behavior and performance in organizations. The purpose of this study was to determine the effect of quality of work life, leadership, and perceived organizational support on organizational commitment. Respondents are employees in a company engaged in retail in the city of Surabaya with a total of 149 people. The analysis tool is multiple linear regression. The results of the study stated that the quality of work life, leadership, and perceived organizational support have a significant influence partially and simultaneously on organizational commitment.